Metabolites in urine of cattle with experimental bladder lesions and fed bracken fern - Döbereiner, Jürgen; Olson, Carl; Brown, Raymond R.; Price, James M.; Yess, Norma (Pesquisa Agropecuaria Brasileira, 2024)
In attempts to detect the presence of urinary metabolites which may have a relationship to the cause of bovine enzootic hematuria, calves were fed a basal diet supplemented with fresh or dried bracken fern (Pteridiun aquilinum (L.) Kuhn) and the urinary excretion of phenols, aromatic amines and fluorescent substances was compared qualitatively by paper chromatography with urines from calves receiving only the basal diet. In addition, quantitative analyses were made for a number of tryptophan metabolites, creatinine and 4-pyridoxic acid. No consistent qualitative or quantitative differences were observed between the bracken-fed animals and contros over a 13 month period. Neither were significant seasonal differences observed in either group. Clinical studies on these animals showed no change in blood cell counts or bleeding time. The four animals inoculated in the bladder with bovine cutaneous papilloma preparations developed tumor-like lesions in their urinary bladders.